Førstefødtlæstadianernes selvrepresentasjon. En analyse av to brosjyrer - Andreassen, Bengt-Ove (Nordlit, 2012)
In 1992 and 2010 the group within the Laestadian tradition labeled “the firstborns” or “the firstborn group” published brochures in which they express their beliefs and identity. Using a discourse analytical approach the article aims to examine the Firstborn’s selfrepresentation in these brochures. A goal is to investigate whether or not the Firstborn self-representation has changed in the period between the two brochures. A main argument is that the group’s mediation and way of representing themselves in 2010 is characterized by a new use of established concepts which point to a possible secession from the Norwegian State Church and the establishment of a separate independent religious organization.